2016
DOI: 10.18869/acadpub.aassjournal.4.4.21
|View full text |Cite
|
Sign up to set email alerts
|

Single and Concurrent Effects of Endurance and Resistance Training on Plasma Visfatin, Insulin, Glucose and Insulin Resistance of Non-Athlete Men with Obesity

Abstract: The purpose of the present study was to investigate the effect of endurance (ET), resistance (RT) and concurrent training (CT) on plasma levels of visfatin, insulin, glucose and insulin resistance of non-athlete men with Obesity. It was a semi-experimental study. Thirty six men [age: 21.48 (0.25), and BF%: 27.39 (0.52)], voluntarily participated in this study after public announcement in university. Main inclusion and exclusion criteria was healthy (no physical illness and inability), obesity [based on WHO's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…Clinically, the results of periodization are relevant, as they suggest signi cant reductions in insulin resistance indicators in a population at metabolic risk. In general, these positive effects can be effective in the prevention and treatment of obesity, as well as DM2 and other diseases, by promoting adjustments in adipocytokines and other metabolic markers[30].The strengths of this blind randomized clinical trial were the control of the aerobic training variables, the maintenance of the relative intensity in the NG, and the gradual increase of intensity in the PG over the mesocycles, both adjusted by the resting heart rate and considered a control method of low-cost. The progression of intensity and similarity in the training volume, is another strength, as it allows to verify the effects of different forms of periodization in the combined training program in an equal way.…”
mentioning
confidence: 99%
“…Clinically, the results of periodization are relevant, as they suggest signi cant reductions in insulin resistance indicators in a population at metabolic risk. In general, these positive effects can be effective in the prevention and treatment of obesity, as well as DM2 and other diseases, by promoting adjustments in adipocytokines and other metabolic markers[30].The strengths of this blind randomized clinical trial were the control of the aerobic training variables, the maintenance of the relative intensity in the NG, and the gradual increase of intensity in the PG over the mesocycles, both adjusted by the resting heart rate and considered a control method of low-cost. The progression of intensity and similarity in the training volume, is another strength, as it allows to verify the effects of different forms of periodization in the combined training program in an equal way.…”
mentioning
confidence: 99%
“…Screening of the titles and abstracts excluded a further 33,344 articles and, therefore, 290 full texts were retrieved. Finally, 24 papers were included in the study [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], of which the two following papers related to the same study conducted on the same population and the same intervention but reported on the different outcomes: Nunes et al [ 47 ] and Martins et al [ 48 ]. Moreover, one manuscript was published in two journals [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies were designed as randomised trials and published between 2005 [ 45 ] and 2021 [ 23 ]. Most studies were performed in Asia (eight in Iran [ 17 , 18 , 20 , 37 , 38 , 41 , 42 , 44 , 46 ] two in Japan [ 19 , 45 ], and one in South Korea [ 24 ]); six studies were conducted in Europe (two in Poland [ 14 , 23 ], one each in Denmark [ 21 ], Finland [ 40 ], Greece [ 15 ], and Norway [ 43 ]); three in South America (Brazil [ 25 , 47 , 48 ]); and three studies were performed in Australia and Oceania (two in Australia [ 16 , 39 ] and one in New Zealand [ 22 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important detail is that the participants in this study [29] and ours were not previously trained, which enlarges and/or limits the zone of training regardless of the periodization model. In general, these positive effects can be effective in the prevention and treatment of obesity, as well as DM2 and other diseases, by promoting adjustments in adipocytokines and other metabolic markers [30].…”
Section: Discussionmentioning
confidence: 99%